An Integrative Method for Characterizing Marine Habitat Features Associated With Predation: A Case Study on Juvenile Steller Sea Lions (Eumetopias jubatus) - Bishop, Amanda M.; Brown, Casey L.; Sattler, Renae; Horning, Markus (Frontiers in Marine Science, 2020)
Characterizing the habitat associated with predation events can inform on predator-prey dynamics. Despite being evaluated extensively in terrestrial systems, quantifying and characterizing the role predation plays in upper trophic marine ecosystems is challenging due to the cryptic nature of pelagic predators and the difficulty of observing predatory behavior. We developed a multi-step method to characterize habitat associated with predation that integrates data from post-mortem pop-up style mortality transmitters, and data from traditional external tracking devices, both of which use the Argos satellite system. In our case study with juvenile Steller sea lions (SSL, Eumetopias jubatus) in the Gulf of Alaska, 20 mortality events were previously described, of which 18 were attributed to predation. The locations of 13 of these at-sea predation events with post-mortem tracking data were estimated, with spatial uncertainty calculated using movement-based approaches of backwards step-length and state-space modeling. We then generated a Mortality Occurrence Probability Distribution (MOPD), resampled points within the MOPD based on isopleth weighting, and extracted habitat variables (i.e. slope, depth, distance to haulout-rookery) associated with these locations. This final dataset represented ‘case’ points (n=115) in terms of predation and was compared to the habitat associated with ‘control’ points (n=1000), locations within juvenile SSL distribution in this region (i.e. population home range), in a resource-selection function (GAM). Predation events were associated with habitats characterized by greater depths and moderate distances from SSL haulouts and rookeries. This information enabled us to generate a risk-map for juvenile SSL in the Gulf of Alaska, spatially representing areas of high predation probability. Our study provides important information about threats to this vulnerable age-class, and establishes a novel approach to characterizing risk in marine ecosystems that can be applied to other management and ecosystem concerns.